Aplikasi Fotokatalis TiO2 Dan Alternatifnya Untuk Degradasi Pewarna Sintesis Dalam Limbah Cair - Dui Yanto Rahman; Rita Sulistyowati (Universitas PGRI Palembang, 2023)
Liquid waste containing synthetic dyes is a significant environmental problem, particularly in the textile industry, such as batik waste. Recent studies have shown the potential of TiO2 photocatalysis in reducing color and Chemical Oxygen Demand (COD) in such waste. In addition to TiO2, ZnO nanoparticles and ZrO2-TiO2 composites have also been tested as alternative photocatalysts for the degradation of synthetic dyes. The use of immobilized TiO2 nanoparticles on various substrates such as plastic sheets, hydrogels, or hybrid films has increased the efficiency of photocatalytic processes and allowed for the separation of photocatalysts from the waste after treatment. Furthermore, the combination of TiO2 with additives such as Mg, Ag, and Fe has enhanced the photocatalytic performance in removing synthetic dyes from wastewater. The use of TiO2-based photocatalytic membranes also enables simultaneous filtration and degradation of pollutants in wastewater treatment. In addition to degrading synthetic dyes, TiO2 photocatalysis has been successfully used to remove natural dyes like Congo red from industrial wastewater. Recent studies have also explored new synthesis methods to obtain TiO2 photocatalysts with enhanced properties, such as TiO2 nanocoating on nanocomposites or TiO2 nanocoating on porous materials. Overall, these studies demonstrate that TiO2 photocatalysis has great potential in liquid waste treatment, particularly in the degradation of synthetic dyes found in textile industry waste like batik waste.